Electronic Media and Impact of Advancement in Information Technology - Chaudhary, Dr. Muhammad Umair; Ghani, Abdul; Jabeen, Shehla (Journal of Peace, Development and Communication, 2020)
The present study shall discuss and explore the advancement of Information Technology and its usage in electronic media. It will also elaborate the technological advancement, and development has impacted media particularly electronic media including radio, newsreels, television, and film, etc. Information Technology has been influential due to its rapid advancement and progression. It has also reshaped the way information is disseminated on different forms of electronic media. To gauge the impact of advancement in Information Technology on electronic media, a survey method was used and interviews were conducted from IT professionals, journalists students, etc. All forms of information technology have virtually created an impact on society. However, the electronic media industry has taken some time to adopt technological advancements, changes, and development. The emergence of new ways, techniques resultantly increased the viewership, and resultantly transmission of electronic media has gone up dramatically.